The zookeeper's wife : [compact disc, unabridged] : a war story - Ackerman, Diane, 1948- (BBC Audiobooks America, 2007)
During WWII, heroes emerged from the most unexpected places. In this moving account, Ackerman brings to life the true story of what happened to the human and animal residents of the Warsaw Zoo when the Nazi army invaded.